Case report: A case of acute mastitis associated with reactive cutaneous capillary endothelial proliferation after camrelizumab treatment: A new immune-related adverse event - Wu, Ping-Shang; Xiong, Dan; Feng, Yang-Bo; Xiang, Luan; Zhu, Jian (Frontiers in Immunology, 2022)
Lung cancer is a malignant tumor with the highest morbidity and mortality rate worldwide, and it seriously endangers human health. In recent years, immunotherapy has been widely used in lung cancer and has achieved great benefits, especially the application of promoting antitumor immune defense. However, immune-related adverse events (irAEs) caused by immune checkpoint inhibitors have received increasing attention, which largely limits their use. We report the first case of new acute mastitis caused by anti-PD1 inhibitors due to lung adenocarcinoma. A 65-year-old female patient came to our hospital for treatment with cough and shortness of breath for one month. Chest CT showed that the malignant tumor in the lower lobe of the right lung with pleural effusion had metastasized to many places, and then pleural effusion was taken for pathological examination. Pathological examination indicated that the pleural fluid originated from lung adenocarcinoma. Subsequently, the patient received platinum-containing dual-agent chemotherapy (carboplatin and pemetrexed disodium) combined with immunotherapy (camrelizumab). During treatment, the patient developed known adverse events and unreported acute mastitis. After stopping camrelizumab, the patient's mastitis gradually improved. Our case shows that acute mastitis might be a new adverse event after the use of camrelizumab. Since this new adverse event has not been reported, we hope that oncology medical workers can obtain insight from our case and use it as a reference for the identification and management of irAEs.